The effect of Zexie decoction on vestibular and auditory function in DDAVP-induced endolymphatic hydrops of Guinea pigs - Ji, Renlong; Xu, Yanchang; Li, Kang; Jiang, Wen; Li, Yuan; Zeng, Jianwei; Li, Wei; Wang, Caiji; Zhao, Zeqi; Li, Yalan; Konduru, Naveena; Liu, Wen; et al. (Frontiers in Neurology, 2025)
ObjectiveTo investigate the effects of Zexie decoction on vestibular and auditory function in guinea pigs with endolymphatic hydrolysis induced by desmopressin. Methods: Sixty guinea pigs were randomly and evenly divided into four groups, each group has 15 guinea pigs: normal control group, DDAVP group, DDAVP modeling combined with Zexie Decoction group, and DDAVP combined with Double Zexie group. At 7 and 14 days, bone-conducted cervical vestibular evoked myogenic potential tests, auditory brainstem responses, and distortion-product otoacoustic emissions were conducted on each group of guinea pigs to evaluate their vestibular and auditory function quantitatively. After functional testing, the outer hair cells were observed by scanning electron microscope. On day 14, one guinea pig was randomly selected from both the normal control group and DDAVP group to verify the successful establishment of the model using gadolinium-enhanced magnetic resonance imaging of the inner ear.ResultsWe conducted BC-cVEMP, ABR, and DPOAE tests on guinea pigs, and the results showed that DDAVP did affect vestibular function and hearing in guinea pigs. Analyses were performed from those results that were statistically significant, Zexie Decoction improved DDAVP-induced vestibular dysfunction and hearing loss dose-dependently, though complete reversal was not achieved. About scanning electron microscopy, outer hair cells of the DDAVP group showed significant loss and cilia lodging, however, treatment with Zexie decoction can alleviate the loss of outer hair cells and the lodging of cilia. When the outer hair cells were exposed to DDAVP for a long time, the improvement effect of Zexie decoction was not as obvious as before.ConclusionThe extent of improvement correlates with the concentration and dosage of Zexie Decoction. Even at double the dosage, Zexie Decoction only partially mitigates the decline in vestibular and auditory function induced by DDAVP, falling short of complete reversal.